Familial aggregation of streptomycin ototoxicity: autosomal dominant inheritance?. Issue 5 (October 1983) - Viljoen, D L; Sellars, S L; Beighton, P
Abstract : Eight members of a large kindred of mixed ancestry from a remote rural area of South Africa were investigated for deafness. In each, severe permanent perceptive hearing loss had developed during antituberculous therapy with streptomycin sulphate in conventional doses. Although unproven by the data available in this study, the familial aggregation and pattern of distribution of sensitivity to streptomycin suggested autosomal dominant inheritance.